Analisis Perubahan Struktur Ekonomi Dan Penentuan Sektor Unggulan Kabupaten Pelalawan Provinsi Riau Tahun 2009-2012 - Kusumaningsih '; Susy Edwina; Yusmini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The process of change inthe economicstructurecharacterized by, the decline inthe share ofthe primary sector, the increase in theshare ofthe secondary sector and the share ofthe tertiary sectoralso contributed totheincrease in linewitheconomicgrowth. Characteristics of economic growth in Pelalawan regency indicated by the presence of several leading sectors in the region.The purposeof this studyisto analyze theshift ofeconomic structureandidentify  the leading sectors inPelalawan regency the period 2009-2012. The analytical toolusedis theshiftshareanalysis (SS) and the method oflocationquotient (LQ). The data usedaresecondary dataobtainedfromthe Central Statistics Agency. The results showed thatthere are twosectorswhichhaveseveral advantages. These sectorsarethe manufacturing sectorbased onindicators ofGDPand construction sectorbased on indicators oflabor. These sectors arecategorizedassectors withhighgrowth, highcompetitivenessand a sector basis. While theagriculturalsector which dominatesthe economicstructureinthis regionhas alowgrowthbut ithas ahighcompetitivenessandasector basis. The economic structure in Pelalawan regency has shiftedfromthe primary sectorto thesecondarysector, althoughthe rate of shiftsis stillrelativelysmall, characterized bythe percentagecontributionofthe primary sectorhas declined, while thecontribution ofthe secondary sector and thetertiaryincreased. Key word : economic structure, GDP, labor, leading sectors